2014
DOI: 10.1080/13547860.2014.908539
|View full text |Cite
|
Sign up to set email alerts
|

Farmland loss and livelihood outcomes: a microeconometric analysis of household surveys in Vietnam

Abstract: Although there has been much discussion in the literature about the impacts of farmland loss (due to urbanization) on household livelihoods, no econometric evidence of these effects has been provided thus far. This paper, hence, is the first to quantify the effects of farmland loss on household livelihood outcomes in peri-urban areas of Hanoi, Vietnam. Our study found no econometric evidence for negative effects of farmland loss on either income or expenditure per capita. In addition, the results show that far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 25 publications
5
27
0
Order By: Relevance
“…Household size had a negative effect on per capita income in both models in Table 5. This finding is in line with several studies in rural Honduras (Jansen, Pender, Damon, Wielemaker, & Schipper, 2006) and peri-urban Vietnam (Tran, Lim, Cameron, & Van, 2014),which show that having more dependent members, and more family members in general, seems to reduce per capita income. Keeping all other variables constant, Model 1shows that an additional family member results in a decrease in annual per capita income of about 2.643 million VND (125.86 USD).…”
Section: Determinants Of Household Welfaresupporting
confidence: 91%
“…Household size had a negative effect on per capita income in both models in Table 5. This finding is in line with several studies in rural Honduras (Jansen, Pender, Damon, Wielemaker, & Schipper, 2006) and peri-urban Vietnam (Tran, Lim, Cameron, & Van, 2014),which show that having more dependent members, and more family members in general, seems to reduce per capita income. Keeping all other variables constant, Model 1shows that an additional family member results in a decrease in annual per capita income of about 2.643 million VND (125.86 USD).…”
Section: Determinants Of Household Welfaresupporting
confidence: 91%
“…Larger labor endowments push rural households into nonfarm activities in most countries . Younger members are more likely to participate in offfarm activities in China (Huang et al, 2009) and Vietnam (Tuyen et al, 2014a). Men are more likely than women to be wage earners in off-farm activities, while women are more likely than man to engage in nonfarm self-employment in Vietnam (Tuyen et al, 2014b), Ghana and India (Mattingly and Gregory, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…With respect to income and livelihoods, Le (2007) states that only 16.1 per cent of households surveyed stated that their income increased after land loss. Other studies have shown that farmland loss has indirect positive effects on livelihoods via its positive effects on non-farm participation in urbanising areas (Tuyen et al, 2014b). changes to livelihood vary greatly under the effects of urbanisation.…”
Section: Livelihood Dynamics: a Literature Reviewmentioning
confidence: 99%
“…Livelihoods in peri-urban zones are dynamic as a result of advantageous access to urban labour markets (Wit, 2011;Tuyen et al, 2014aTuyen et al, , 2014bTacoli, 2004). Almost all households in this study pursue a diversified livelihood in which farm and non-farm activities are combined.…”
Section: Livelihood Dynamics After Land Lossmentioning
confidence: 99%
See 1 more Smart Citation